Reproductive And Sexual Tract Infections Among Married Female Youth in An Urban Slum of Mumbai - Kazi, Yasmeen K; Shenoy, Anita G; Velhal, Gajanan; Suryawanshi, Sudam R (National Journal of Community Medicine, 2013)
Introduction: The issues faced by the youth (15 – 24 years) today like illiteracy, unemployment, high risky behavior can result in adverse economic, social and political consequences. Young women face additional problems, like malnutrition, anemia. They are forced into early marriage and child bearing. Hence, this study was carried out to study the Sexual & Reproductive Tract Infections among the Married Female Youth, in an Urban Slum of Mumbai. Methodology: Married Female Youth in the age group 15 – 24 who attended the Out Patient Department at the Urban Health Centre, Shivaji Nagar during the period from October to December 2011 were included in the study ( n= 192). Women were enquired about their socioeconomic status, including their age at marriage, age at 1st childbirth, number of children, spacing between children and history of Reproductive Tract Infection/ Sexually Transmitted Infection with the help of pretested, preformed, semi structured interview questionnaire. Results: It was found that women were married early (mean = 16.90, S.D=2.37) & even had their 1st child at an earlier age (mean 18.43, S.D=1.94). Factors, such as early age at marriage ( p= 0.059), early age at 1st childbirth ( p = 0.038), & less spacing between children ( p = 0.0316) was seen to have an influence on the Reproductive health of the women.